The Optimal Forest Management of an Even-Aged Stand: The Biological Rotation versus the Land Expectation Value - Andres Susaeta; Chris Demers (EDIS, 2019)
This 4-page fact sheet written by Andres Susaeta and Chris Demers and published by the UF/IFAS School of Forest Resources and Conservation provides a guide for forest landowners, managers, and stakeholders in conducting a valuation of timber investments. It reviews and provides examples of two different approaches for determining the optimal rotation age of even-aged forest stands. These methods can help forest landowners and managers in making forestry investment decisions. https://edis.ifas.ufl.edu/fr424